Peningkatan Kemampuan Pemecahan Masalah Melalui Pendekatan Matematika Realistik - Kairuddin Kairuddin; Wafiq Azizah Br. Sinaga (Departement of Mathematics Education, 2023)
The study aims to improve problem-solving skills with a realistic mathematical approach in the students of the 8th grade of the State High School. This study is a Class Action Research (PTK) that consists of 2 cycles, with each cycle consisting of 2 meetings. The subjects in this study were 32 students of class VIII-3 SMP Negeri 2 Medan. At the classical initial test 1 (3.7%) students are rigorous and the average student initial test in the category is very low. On cycle I experienced an improvement of the classically acquired 23 (71%) students of a rigorous and a student test average of 65.98 with a level of proficiency in the medium category. In the II cycle experienced improvements classically acquired 28 (87,5%) students were rigorous and a student test average of 77.99 with a level of ability in the middle category. Thus, it can be concluded that the application of realistic mathematical approaches can improve students' ability to solve math problems.